Analisis Yuridis Penerapan Barcode My Pertamina Dalam Pembelian BBM Bersubsidi Di Kabupaten Semarang - Drajad Candra Putra; Arista Candra Irawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The distribution of subsidized fuel in Indonesia often faces various challenges, especially in terms of targeting accuracy and distribution supervision. The government through PT Pertamina (Persero) has implemented a digitalization system for purchasing subsidized fuel using the My Pertamina application barcode as an effort to increase efficiency and accountability. This study aims to analyze the legal aspects of the implementation of the My Pertamina barcode system in purchasing subsidized fuel, especially in the Semarang Regency area. The method used is a normative legal approach with a study of literature and related laws and regulations, such as Law Number 22 of 2001 concerning Oil and Gas, Presidential Regulation Number 191 of 2014 concerning the Provision, Distribution, and Retail Selling Prices of Fuel, and technical regulations from the Downstream Oil and Gas Regulatory Agency (BPH Migas). The results of the study indicate that although the implementation of the My Pertamina barcode has a strong legal basis, its implementation still faces challenges in the form of digital infrastructure gaps, limited technological literacy of the community, and potential discrimination in access for certain groups. Therefore, it is necessary to strengthen derivative regulations and supporting policies that guarantee fairness and affordability in purchasing subsidized fuel.